Biosynthetic Mechanisms of Secondary Metabolites Promoted by the Interaction Between Endophytes and Plant Hosts - Li, Zhaogao; Wen, Weie; Qin, Ming; He, Yuqi; Xu, Delin; Li, Lin (Frontiers in Microbiology, 2022)
Endophytes are a new microorganism resource with potential pharmaceutical values. The interactions between endophytes and their host plants not only promote the growth and development of each other but also drive the biosynthesis of many new medicinal active substances. In this review, we summarized recent reports related to the interactions between endophytes and hosts, mainly regarding the research progress of endophytes affecting the growth and development of host plants, physiological stress and the synthesis of new compounds. Then, we also discussed the positive effects of multiomics analysis on the interactions between endophytes and their hosts, as well as the application and development prospects of metabolites synthesized by symbiotic interactions. This review may provide a reference for the further development and utilization of endophytes and the study of their interactions with their hosts.